Experimental Research on Properties of Naval Brass Castings - Turker, M.; Comert, Z. Yasar; Kisasoz, A.; Guler, K. Altug (WALTER DE GRUYTER GMBH, 2016)
Naval brasses consisting of the alpha-beta duplex phases are a special kind of Cu-Zn alloys. They are known to have excellent corrosion resistance to sea water and marine conditions. The aim of this study is the investigation of properties and behaviours of naval brass parts formed by different casting processes. A medium leaded naval brass alloy with 60 % Cu, 39 % Zn and 1 % Pb approximate composition was used. Several samples were subjected to mechanical testing by means of tensile and hardness tests. Light optical microscopy with image analyser and scanning electron microscopy were used for microstructure observations. The corrosion test was applied in sea water conditions. Results reveal that besides hot forging also casting is a very suitable technique for naval brass shaping. Casting does not have a negative effect on the most important property corrosion resistance. Furthermore, the obtained mechanical properties are satisfactory.
Keywords: BEHAVIOR; COPPER; BETA; DEZINCIFICATION; Metallurgy & Metallurgical Engineering